Hexagonal BN‐Assisted Epitaxy of Strain Released GaN Films for True Green Light‐Emitting Diodes. Issue 21 (27th September 2020) - Liu, Fang; Yu, Ye; Zhang, Yuantao; Rong, Xin; Wang, Tao; Zheng, Xiantong; Sheng, Bowen; Yang, Liuyun; Wei, Jiaqi; Wang, Xuepeng; Li, Xianbin; Yang, Xuelin; et al.
Abstract: Epitaxial growth of III‐nitrides on 2D materials enables the realization of flexible optoelectronic devices for next‐generation wearable applications. Unfortunately, it is difficult to obtain high‐quality III‐nitride epilayers on 2D materials such as hexagonal BN (h‐BN) due to different atom hybridizations. Here, the epitaxy of single‐crystalline GaN films on the chemically activated h‐BN/Al2 O3 substrates is reported, paying attention to interface atomic configuration. It is found that chemical‐activated h‐BN provides BON and NO bonds, where the latter ones act as effective artificial dangling bonds for following GaN nucleation, leading to Ga‐polar GaN films with a flat surface. The h‐BN is also found to be effective in modifying the compressive strain in GaN film and thus improves indium incorporation during the growth of InGaN quantum wells, resulting in the achievement of pure green light‐emitting diodes. This work provides an effective way for III‐nitrides epitaxy on h‐BN and a possible route to overcome the epitaxial bottleneck of high indium content III‐nitride light‐emitting devices. Abstract : Epitaxy of single‐crystalline GaN films is performed on hexagonal BN (h‐BN)/sapphire substrates. This success is achieved through chemical activation on h‐BN, which generates NO bonds, and thus provides nucleation sites for Ga‐polar GaN. Subsequently, pure green InGaN‐based light‐emitting diodes are fabricated with a considerable increase of indium incorporation, manifesting a great potential in long wavelength light‐emitting diodes.